2020
DOI: 10.1128/mbio.00810-20
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Outer Tegument Component UL11 from Herpes Simplex Virus 1 Is an Intrinsically Disordered, RNA-Binding Protein

Abstract: A distinguishing morphological feature of all herpesviruses is the multiprotein tegument layer located between the nucleocapsid and lipid envelope of the virion. Tegument proteins play multiple roles in viral replication, including viral assembly, but we do not yet understand their individual functions or how the tegument is assembled and organized. UL11, the smallest tegument protein, is important for several distinct processes in replication, including efficient virion morphogenesis and cell-cell spread. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 95 publications
(186 reference statements)
0
40
0
Order By: Relevance
“…The tegument protein UL11 from Herpes simplex virus 1 (HSV-1) has been shown to undergo LLPS in vitro, based on macroscopic and time-lapse imaging by a stereo light microscope [196]. The protein is endowed with a high degree of structural disorder and multivalent interaction properties.…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
“…The tegument protein UL11 from Herpes simplex virus 1 (HSV-1) has been shown to undergo LLPS in vitro, based on macroscopic and time-lapse imaging by a stereo light microscope [196]. The protein is endowed with a high degree of structural disorder and multivalent interaction properties.…”
Section: Examples Of Viral Proteins Undergoing Llps Associated With Vmentioning
confidence: 99%
“…Loss of, or reduced function in, one pathway could then be compensated by enhancing the activity of another. Alternatively, Metrick and colleagues [ 45 ] recently proposed that all inner and outer HSV-1 tegument proteins contain intrinsically disordered regions (IDRs), of variable length, which enable them to undergo phase separation, forming a spherical biomolecular condensate that helps drive envelopment [ 186 ]. If the tegument exists (at least in part) as a biomolecular condensate, it would be extremely tolerant to loss or change in expression level of many of its constituents, and potentially quite variable in its final composition, as multiple tegument or even host proteins could contribute to condensate formation [ 45 , 187 , 188 ].…”
Section: Capsid Transport and Envelopment In The Cytoplasmmentioning
confidence: 99%
“…Alternatively, Metrick and colleagues [ 45 ] recently proposed that all inner and outer HSV-1 tegument proteins contain intrinsically disordered regions (IDRs), of variable length, which enable them to undergo phase separation, forming a spherical biomolecular condensate that helps drive envelopment [ 186 ]. If the tegument exists (at least in part) as a biomolecular condensate, it would be extremely tolerant to loss or change in expression level of many of its constituents, and potentially quite variable in its final composition, as multiple tegument or even host proteins could contribute to condensate formation [ 45 , 187 , 188 ]. Of possible relevance to this model, we found that the tegument protein UL48p (VP16) ( Table 1 ) binds in vitro to a peptide with the sequence of the gH cytoplasmic tail, but only at 37 °C when that peptide was in a disordered state [ 35 , 36 ].…”
Section: Capsid Transport and Envelopment In The Cytoplasmmentioning
confidence: 99%
“…The linear dsDNA genome is covered with an icosahedral capsid. The layer of protein between the capsid and outer envelope, collectively termed the tegument, is unique to herpesvirus ( Metrick et al, 2020 ). Twenty-six tegument proteins have been found in HSV-1 ( Loret et al, 2008 ; Kelly et al, 2009 ; Kukhanova et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%